PENILAIAN SIKAP PENDIDIKAN AGAMA ISLAM DI SDIT ISTIQOMAH LEMBANG BANDUNG BARAT TAHUN PELAJARAN 2018-2019 - A Wandi; Chaerul Rochman; Nina Nurmila (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The purpose of this study was to determine the assessment of affective attitudes of students in learning PAI at SDIT Istiqomah Lembang, Bandung Barat district. This is very important to be discussed and known by every educator, given that the teacher's task is not only limited to teaching, but also evaluates, and one of them is the assessment of affective attitudes related to spiritual and social attitudes. The research method used in this research is descriptive explorative. The assessment technique used is the assessment sheet between students and the instruments used are checks and rating scales with class-based sociometric techniques consisting of fourteen indicators. The conclusions of this assessment are: 1) There are four students who are in a good category and eighteen students are in a very good category, 2) There are nine indicators of affective aspects which are in the good category namely indicators 4, 6, 8, 9, 10, 11, 12, 13, 14, and there are five indicators in the excellent category, namely indicators 1, 2, 3, 5, 7.